Gas-Phase Reactions of the Rhenium Oxide Anions, [ReOx]− (x = 2–4) with the Neutral Organic Substrates Methane, Ethene, Methanol and Acetic Acid. Issue 3 (June 2015) - Canale, Valentino; Zavras, Athanasios; Khairallah, George N.; d'Alessandro, Nicola; O'Hair, Richard A.J.
The ion–molecule reactions of the rhenium oxide anions, [ReO x ] − ( x = 2–4) with the organic substrates methane, ethene, methanol, and acetic acid have been examined in a linear ion trap mass spectrometer. The only reactivity observed was between [ReO2 ] − and acetic acid. Isotope-labelled experiments and high-resolution mass spectrometry measurements were used to assign the formulas of the ionic products. Collision-induced dissociation and ion–molecule reactions with acetic acid were used to probe the structures of the mass-selected primary product ions. Density functional theory calculations [PBE0/LanL2DZ6-311+G(d)] were used to suggest possible structures. The three primary product channels observed are likely to arise from the formation of the metallalactone [ReO2 (CH2 CO2 )] − ( m/z 277) and H2, [CH3 ReO2 (OH)] − ( m/z 251) and CO, and [ReO3 ] − ( m/z 235), H2 and CH2 CO.